Young Barley Indicates Antitumor Effects in Experimental Breast Cancer In Vivo and In Vitro - Kubatka, Peter; Kello, Martin; Kajo, Karol; Kruzliak, Peter; Výbohová, Desanka; Šmejkal, Karel; Maršík, Petr; Zulli, Anthony; Gönciová, Gabriela; Mojžiš, Ján; Kapinová, Andrea; Murin, Radovan; et al. (Nutrition and cancer, 2016)
The effect of dietary administered young barley containing a mixture of phytochemicals to female rats for the prevention of N-methyl-N-nitrosourea-induced mammary carcinogenesis was evaluated. After carcinogen administration (14 wk), mammary tumors were removed and prepared for histopathological and immunohistochemical analysis. Moreover, in vitro evaluation of possible mechanisms in MCF-7 breast cancer cell line was performed. Barley (0.3%) demonstrated mild antitumor effect in mammary carcinogenesis, yet 3% barley did not further improve this effect. Immunohistochemical analysis of rat tumor cells in treated groups showed significant increase in caspase-3 expression and significant reduction in Ki67 expression. In addition, 3% barley significantly decreased dityrosine levels versus control. Barley in higher dose significantly decreased serum low-density lipoprotein-cholesterol in rats. In vitro studies showed that barley significantly decreased survival of MCF-7 cells in 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and significantly decreased 5-bromo-20-deoxyuridine incorporation versus control. Barley prevented cell cycle progression and extended incubation with barley showed significant increase in the percentage of annexin V/propidium iodide-positive MCF-7 cells. Our results propose an antitumor effect for the mixture of phytochemicals present in young barley in a breast cancer model.
Keywords: Anticarcinogenic Agents; flavonoidy; Animals; ječmen (rod); nádory prsu; apoptóza; proliferace buněk; Female; Apoptosis; ženské pohlaví; Flavonoids; MFC-7 buňky; lidé; Lipid Metabolism; Mammary Neoplasms, Experimental; MCF-7 Cells; methylnitrosomočovina; Breast Neoplasms; antikarcinogenní látky; metabolismus lipidů; Rats, Sprague-Dawley; Humans; potkani Sprague-Dawley; Cell Proliferation; Methylnitrosourea; Hordeum; zvířata; experimentální nádory mléčných žláz